Application Design of Stock Inventory of Meatball Serving Ingredients for Anhel MSME Bakso - Muhamad Hesky Ramadan; Roni Ilham Subagja; Asep Suherman; Isak Ramlan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
Inventory management systems are a cornerstone of operational efficiency for MSMEs (Micro et al.). This study aims to develop and implement an inventory management information system for MSME Bakso ANHEL. The system, which enables real-time inventory tracking, order optimization, and improved supply chain efficiency, is a testament to the transformative power of information technology in enhancing the competitiveness of MSMEs. The findings of this study can provide valuable insights for MSME Bakso ANHEL and other similar businesses, equipping them with the tools to address inventory management challenges. The strategic use of information technology is a game-changer for micro, small, and medium enterprises (MSMEs).